Comparison Of BRI Bank Portfolio Performance With BSI In Investment Decisions For Investors (2021) - Fauzul Hakim Hasibuan; Dilla Amanda; Munawar Khalil Nasution; Putri Zahratul Jannah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study sets out to comprehensively analyze the viability of investing in Islamic banks as a sound financial decision and to evaluate their competitiveness in comparison to conventional bank portfolios. To achieve this objective, the research encompasses a diverse set of financial instruments and performance metrics. The research sample primarily revolves around the stock prices of two prominent banks in Indonesia, namely BRI (Bank Rakyat Indonesia) and BSI (Bank Syariah Indonesia), during the year 2021. In addition to these, the IHSG (Indonesia Stock Exchange Composite Index) serves as the market return indicator for BRI's portfolio. Furthermore, the benchmark interest rate from Indonesia is utilized as the risk-free rate (Rf) in the calculations. For BSI's portfolio, SBIS (Syariah Benchmark Indonesia) is employed as an alternative to Rf, and JII (Jakarta Islamic Index) is designated as the market return indicator. The assessment of the portfolio performance is conducted using three key index formulas: the Treynor index, the Sharpe index, and the Beta Jensen index. Importantly, the research findings reveal that BSI demonstrates superior performance compared to BRI when assessed using these three index formulas. This evaluation was conducted using the Security Characteristic Line (SCL) and the Security Characteristic Adjustment Performance Model (SCAPM) method, as opposed to BRI's portfolio evaluation using the more conventional CAPM (Capital Asset Pricing Model) formula. These results suggest that investing in Islamic banks, represented by BSI in this study, can indeed yield favorable outcomes, highlighting their potential as a competitive and promising investment option in the financial landscape.